Challenges of Deaf and Hard-of-Hearing Students in English Learning in Higher Education - Yintong Lu (Canadian Journal for New Scholars in Education)
Following the trend of inclusive education in China during the past decade, a growing number of deaf and hard-of-hearing (DHH) students have entered regular tertiary institutions. Learning English as an additional language presents challenges to these DHH students and relevant research is underdeveloped. To explore the English learning experience of DHH students in regular higher education in China, this research conducted a qualitative case study of three DHH students currently enrolled in regular tertiary education. The research findings show that DHH students face multiple difficulties in English learning including inappropriate instruction and assessment methods, insufficient accommodations and support, and a non-supportive physical learning environment. These factors result in a low level of inclusion in the higher education system. The insights from this research contribute to the ongoing global conversation of inclusive education. It offers a comparative view for Western language educators in developing inclusive English education for DHH students.